Integrasi Teknologi dalam Pengembangan Kurikulum - Irwan Maulana; Ade Sofyan; Rifyal Ahmad Lughowi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The development of information technology has driven significant transformation in the education system which includes curriculum development. This research aims to analyze how technology integration can be optimized in the development of the basic education curriculum, taking into account the dynamics that occur in education. This research method uses a documentation study approach to various literature. This research identifies strategies, challenges and opportunities in implementing educational technology. The research results show that technology integration not only increases the accessibility and effectiveness of learning, but also encourages changes in pedagogical paradigms, the role of teachers, and a curriculum approach that is more adaptive to digital developments. The success of this integration is determined by factors such as progressive education policies, teacher technopedagogical competence, equitable infrastructure, digital literacy, and multi-stakeholder collaboration.